Bcl‐2 overexpression ameliorates immune complex‐mediated arthritis by altering FcγRIIb expression and monocyte homeostasis. Issue 4 (1st April 2013) - Lawlor, Kate E.; van Nieuwenhuijze, Annemarie; Parker, Karen L.; Drake, Sarah F.; Campbell, Ian K.; Smith, Scott D.; Vince, James E.; Strasser, Andreas; Wicks, Ian P.
Abstract : Selective effects of the Bcl‐2 survival pathway on monocyte differentiation and its importance in determining the outcome of autoimmune disease. Abstract : RA is a chronic autoimmune disease characterized by accumulation of inflammatory cells within synovial joints. RA is associated with a failure of apoptosis of infiltrating leukocytes, thought to be a result of overexpression of prosurvival Bcl‐2 proteins. Overexpression of Bcl‐2 in hematopoietic cells can result in spontaneous autoimmunity. We therefore hypothesized that increased Bcl‐2 in the hematopoietic compartment would reduce apoptosis and thereby, exacerbate inflammatory arthritis. Paradoxically, we found that overexpression of Bcl‐2 in mice (vav‐ bcl‐2 ) markedly reduced pathology in antibody‐dependent models of RA (CIA and K/BxN serum transfer arthritis). No such protection was observed in a model of CD4 + T cell‐dependent, B cell‐independent arthritis (mBSA/IL‐1‐induced arthritis). In CIA, vav ‐bcl‐2 Tg mice had lower antibody production to CII, which might explain reduced disease. However, Bcl‐2 overexpression also reduced passive K/BxN serum transfer arthritis. Overexpression of Bcl‐2 caused a monocytosis, with preferential expansion of Ly6C lo monocytes and increased expression of the inhibitory receptor for IgG, FcγRIIb, on leukocytes. Skewing of the myeloid cell population, increases in FcγRIIb, and reduced arthritis were independent of the hypergammaglobulinemia found in vav‐ bcl‐2 Tg mice. These data reveal selective effects of the Bcl‐2‐regulated apoptotic pathway on monocyte differentiation and the expression of FcRs critical for regulation of antibody/immune complex‐mediated disease.